The role of local-ice meltwater in the triggering of an under-ice phytoplankton bloom in an Arctic fjord - Ruiz-Castillo, Eugenio; Verdugo, Josefa; Kirillov, Sergei; Dmitrenko, Igor; Boone, Wieter; Rysgaard, Søren (Frontiers in Marine Science, 2024)
We combined records from moorings, profiler and CTD-transects obtained in an Arctic fjord (Young Sound, Greenland) to assess the effects of local-meltwater input at the beginning of ice-melt, while the fjord was still covered by ice. Results indicate that light penetrated below the ice and was available throughout the sampling period. Melting began at the mouth where the ice and snow layers were thinner. At the mouth, meltwater triggered stratification and onset of an under-ice phytoplankton bloom as shown by an increase in chl-a, fluorescence-CDOM and oxygen saturation. Chl-a was highly correlated with salinity (-0.84) and temperature (0.88) indicating a strong association to the input of meltwater while the maximums in chl-a and oxygen matched the distribution of the meltwater. At the mouth, in the area where the meltwater occurred averaged chla increased from 0.27 to 0.40 mg m -3 and by the end of the record was 3-times greater than the surrounding waters. In the area of the patch of meltwater on 26-28 May, averaged oxygen increased 4-5% during the sampling period. Inside the fjord, patches of meltwater occurred and were advected from the mouth by an in-fjord flow. Within these patches of meltwater chl-a and oxygen saturation increased and by the end of the record were 2-times and 5% higher than the surroundings waters, respectively. This study shows that meltwater and stratification were more important than light for the onset of the under-ice bloom and suggests a significant portion of pelagic primary productivity occurs before ice breakup.